2003
DOI: 10.1074/jbc.m308525200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Plasmodium falciparum Triose-phosphate Isomerase-2-Phosphoglycerate Complex at 1.1-Å Resolution

Abstract: Triose-phosphate isomerase, a key enzyme of the glycolytic pathway, catalyzes the isomerization of dihydroxy acetone phosphate and glyceraldehyde 3-phosphate. In this communication we report the crystal structure of Plasmodium falciparum triose-phosphate isomerase complexed to the inhibitor 2-phosphoglycerate at 1.1-Å resolution. The crystallographic asymmetric unit contains a dimeric molecule. The inhibitor bound to one of the subunits in which the flexible catalytic loop 6 is in the open conformation has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…For seven of these, the high deviation from planarity is maintained despite mutation of the residue. For one of the 16 cases [PDB code 1o5x:Phe150 (26)(27)(28)], the local backbone conformation in the homolog changed, and the nonplanarity was not conserved.…”
Section: Extreme Deviations From Planarity Tend To Be Conserved But Dmentioning
confidence: 99%
“…For seven of these, the high deviation from planarity is maintained despite mutation of the residue. For one of the 16 cases [PDB code 1o5x:Phe150 (26)(27)(28)], the local backbone conformation in the homolog changed, and the nonplanarity was not conserved.…”
Section: Extreme Deviations From Planarity Tend To Be Conserved But Dmentioning
confidence: 99%
“…The open conformation is typically found in apo structures. However, in P. falciparum TIM both open and closed conformations can be observed in a high-resolution (1.1 Å ) ligand-bound structure (Parthasarathy et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The open form has been observed for apo TIM, while ligand binding induces the closure of a loop. However, one ligand-bound structure of TIM from Plasmodium falciparum has been described with both an open and a closed conformation of the loop (Parthasarathy et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies of PfTIM [12][13][14] have shown that the loop6 predominantly occurs in the open conformation, in contrast to other TIMs where it closes on ligand binding when bound to ligands such as glycerol-3-phosphate (G3P), 15 3-phosphoglycerate (3PG), 15 2-phosphoglycolate (PGA) [16][17][18][19][20] and 2-phosphoglycerate (2PG). 21 Loop6 is also in an open conformation in the Trypanosoma brucei enzyme, where the active site has a bound N-hydroxy-4-phosphono-butanamide, 9 which has an additional methylene unit compared to the substrate.…”
Section: Introductionmentioning
confidence: 98%